"Because even us, Arabs, now speak English": Syrian refugee teachers' investment in English as a foreign language. (September 2017) - Karam, Fares J.; Kibler, Amanda K.; Yoder, Paul J.
Abstract: Framed withinDarvin and Norton's (2015) model of investment, this study examined a group of Syrian refugee teachers' ideologies and challenges regarding teaching English as a foreign language (EFL) to Syrian refugee students with interrupted or no prior formal education in three non-formal education (NFE) centers in Lebanon. A qualitative approach using interview data alongside field observations and questionnaire responses was employed to gain a nuanced understanding of the teachers' experiences. Findings from this study suggest that teachers acknowledged the importance of teaching English to their students and did so despite a host of curricular, linguistic, sociolinguistic, and sociocultural obstacles. We suggest that when teachers of refugee students in Education in Emergency (EIE) contexts are invested in teaching EFL, they can assume an agentive role in devising innovative solutions to problems.